Pengaruh Knowledge, Skill dan Tanggung jawab Terhadap Kinerja Pegawai Biro Pengadaan Barang/Jasa Sekretariat Daerah Provinsi Jawa Timur - Brilliant Charisma Fadila Afif; Rudy Handoko; Achluddin Ibnu Rochim (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
The Procurement Bureau of Goods/Services of the Regional Secretariat of East Java Province is still unable to provide optimal service due to several factors such as Knowledge, Skill and Responsibility. The purpose of the study was to analyze the influence of Knowledge, Skill and Responsibility on the Performance of East Java BPBJSD Employees. The study used an explanatory quantitative method. The sample population was 35 East Java BPBJSD Employees. Data collection was done through questionnaires. The analysis technique was through SPSS multiple linear regression. The results of the study proved that there was an influence of Knowledge, Skill and Responsibility on the Performance of East Java BPBJSD Employees partially and simultaneously.